Adverse effects of short-term regimens in multidrug-resistant tuberculosis patients with treatment failure in Central Java, Indonesia - Intan Henda Ardiani; Alma Feriyanti; Intan Zainafree; Fildza Huwaina Fathnin; Muhamad Zakki Saefurrohim (Faculty of Medicine, Universitas Islam Sultan Agung (UNISSULA), Indonesia, 2026)
Recent evidence shows high rates of treatment failure among multidrug-resistant tuberculosis (MDR-TB) patients on short-course regimens. This clinic-based case–control study used Tuberculosis Information System (SITB) data from Central Java, Indonesia (2021–2023) to examine associations between employment status, HIV status, baseline sputum examination, and body mass index (BMI) with specific categories of treatment failure (treatment failure, diagnostic change, regimen modification, loss to follow-up, and death). Overall treatment failure was 70.59%, including 15.3% deaths. Employment status was significantly associated with failure category (p=0.022), with unemployed patients disproportionately experiencing loss to follow-up (82.5%) and death (59.6%). HIV-reactive patients were more likely to undergo regimen modification (p=0.009; 1.8%). Baseline sputum results showed the strongest association (p<0.001): negative sputum was linked to diagnostic change (49.1%) and unknown sputum status to loss to follow-up (66.7%). Low BMI (<18.5 kg/m2) was also associated with failure category (p=0.037), particularly loss to follow-up (75.4%) and death (33.3%). These findings implicate socioeconomic vulnerability, HIV co-infection, absent or negative baseline sputum results, and undernutrition as important determinants of distinct short-course MDR-TB treatment failures and support integrated, patient-centred interventions to improve outcomes.